Somalia : Enhanced Heavily Indebted Poor Countries Initiative-Request for Additional Interim Assistance. (IMF Staff Country Reports; Country Report ;, 2021)
The authorities are requesting additional interim HIPC assistance from the Fund in the amount of SDR 680,000 (Appendix I) to cover the period March 25, 2021- March 24, 2022. The interim HIPC assistance will be applied to cover 100 percent of eligible debt service to the IMF falling due over the 12 months starting from March 25, 2021.